Determinants of Taxpayer Compliance: The Role of Tax Awareness, Financial Penalties, and Tax Authority Attitudes at KPP Pratama South Makassar - Masrullah; Andi Rifki Sunusi G Bandea; Muhammad Khaedar Sahib; Riyanti (Academic Bright Collaboration, 2026)
Purpose – This study aims to examine the influence of tax awareness, financial penalties, and tax authority attitudes on individual taxpayer compliance at KPP Pratama Makassar Selatan. Methods – A quantitative associative technique is used in the investigation. Individual taxpayers were given questionnaires to complete in order to gather primary data. Purposive sampling was used to choose a sample of 100 respondents. Multiple linear regression using SPSS was used to analyse the data. Findings – The simultaneous test shows that the regression model is statistically significant (F = 64.571; p < 0.001), with an R Square of 0.669. Partially, tax awareness has a positive and significant effect on taxpayer compliance (B = 0.233; p = 0.003), financial penalties have a positive and significant effect (B = 0.260; p = 0.003), and tax authority attitudes have the strongest positive and significant effect (B = 0.267; β = 0.360; p < 0.001). These findings suggest that improving taxpayer awareness, implementing consistent and fair penalties, and enhancing the professionalism of tax Authority can contribute to higher taxpayer compliance.” Research implications – This study provides practical implications for tax authorities in designing strategies to improve compliance through behavioral and administrative approaches. Originality – Although the study does not propose a new theoretical model, it contributes by providing empirical evidence from the context of KPP Pratama Makassar Selatan.